ANALISIS PENINGKATAN INDEKS PROPERTIES PADA TANAH LEMPUNG ORGANIK MENGGUNAKAN CAMPURAN ABU SEKAM PADI - william, Jean; Wulandari, Tika Ermita (Universitas Quality, 2024)
Soil is one of the important materials in building a construction. In construction construction, there are many conditions of very low soil carrying capacity, one way to increase the carrying capacity of the soil so that soil stability increases is by mixing rice husk ash. The method used in the rice husk mixture is an experimental method, namely the calculation of water content obtained an average moisture content of 73.17%. The results of the specific gravity analysis obtained an average soil specific gravity of 2.17 grams. The results of the soil liquid boundary analysis were 59.627%, with an additional mixture of rice husk ash of 3% to 55.15% and additional use of rice husk ash of 9% to 51.37%. The results of the analysis of soil plastic boundaries obtained soil plastic limits of 27.67%, with the addition of a mixture of rice husk ash 3% to 32.20% and additional use of rice husk ash 9% to 38.40%. Conclusion Soil in using a mixture of rice husk ash can improve soil stability and soil properteis index improved when mixed with rice husk ash